The Concept Of Competence And Its Development Features In The Linguistic Field/ مفهوم الكفاية وملامح تطوُّره في الدرس اللساني - Alfraidi, Tareq; Ali, Essam (Ijaz Arabi Journal of Arabic Learning, 2024)
This research addresses the concept of competence in linguistics and the essential stages it has gone through since its manifestation at the hands of the linguistic scholar Chomsky until it reached the stage of stability and application. Subsequently, this research analyzed the concepts of competence and performance according to Chomsky and set forth its most essential characteristics according to his perspective. Then, it elucidated the most critical aspects of criticism that the subsequent linguists directed to his concept of competence, citing the essential alternatives they presented to understand this concept. Moreover, the research also treated the idea of communicative competence developed by Dell Hymes as the most prominent alternative to Chomsky’s competence. The research expounded his concept and explained its components and the differences between it and Chomsky’s competence. Furthermore, it explained the criteria that Hymes adopted in measuring the speaker’s competence and his ability to evaluate the performed speech. Consequently, the research dealt with developing communicative competence among those who succeeded Hymes. Hence, this research introduced the sub-competencies that constitute communicative competence according to Canale and Swain and showed their impact on applied linguistics. After that, it dealt with Bachman’s attempt to develop communicative competence through the model he presented under linguistic communicative ability. Finally, the research dilated the model introduced by Celce-Murcia and her colleagues, which is based on the intersection of communicative sub-competencies in discourse competence. The research results showed that the concept of competence passed through several stages that developed and spruced up its characteristics and contributed to stirring it from the theoretical basis to the applied framework. Moreover, Chomsky’s concept of competence differed from that of his successors among the linguists, whose criticisms were more constructive, which led to the development of the idea and made it applicable.